KEPEMIMPINAN WANITA DI DUNIA PUBLIK (Kajian Tematik Hadis) - Bedong, M.Ali Rusdi; Ahmad, Fauziah (LPPM IAIN Parepare, 2018)
This paper discusses the hadith of women's leadership to get a comprehensive and comprehensive understanding of the values contained can provide insight for Muslims, especially women who want to take part in the public sphere. A woman needs to pay attention to the conditions as a leader who has the capability and credibility and still pays attention to existing boundaries and continues to make the hadith of the Prophet as a reference in holding a leadership position.